1994
DOI: 10.1093/infdis/170.1.247
|View full text |Cite
|
Sign up to set email alerts
|

Og4C3 Circulating Antigen: A Marker of Infection and Adult Worm Burden in Wuchereria bancrofti Filariasis

Abstract: A population from the Wuchereria bancrofti-endemic island of Mauke was reevaluated retrospectively by use of the Og4C3 circulating antigen (CAg) enzyme-linked immunosorbent assay to assess active infection in relation to host responses by age and gender. Use of microfilaremia (Mf) alone misclassified 50% of infected people, although CAg and Mf levels were positively correlated. Levels of CAg peaked between those aged 31-60 years; men aged 60 years had a significantly higher CAg prevalence (90%) than women. Fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 4 publications
7
63
2
Order By: Relevance
“…Despite its high sensitivity in finding filarial infection, the Ag-ELISA detected only 1 in 10 carriers with 1-3 mf/ml. Similar false negative results were reported by Chanteau et al (1994);and Dreyer et al (1996) confirmed a filarial 'dance sign' in several individuals with negative antigenaemia. Only 67% were antigen-positive of the mfnegatives with evidence of adult worm infection (Rocha et al 1996).…”
Section: Resultssupporting
confidence: 84%
“…Despite its high sensitivity in finding filarial infection, the Ag-ELISA detected only 1 in 10 carriers with 1-3 mf/ml. Similar false negative results were reported by Chanteau et al (1994);and Dreyer et al (1996) confirmed a filarial 'dance sign' in several individuals with negative antigenaemia. Only 67% were antigen-positive of the mfnegatives with evidence of adult worm infection (Rocha et al 1996).…”
Section: Resultssupporting
confidence: 84%
“…Studies from More and Cooperman (1990), Chanteau et al (1994), and Lalitha et al (1998), concluded that the mAb Og4C3 detects CFA from adult worms, excluding the contribution of MF in the production of CFA. Many studies (including this article), do not agree with this hypothesis (Rocha et al 1996, Nicolas et al 1997, Itoh et al 1999).…”
Section: Study Population and Parasitological Profile -mentioning
confidence: 99%
“…Both CFA tests using mAb Og4C3 and mAb AD.12 are commercially available. Many studies have demonstrated that the CFA detected by mAbs Og4C3 and AD.12 is an indication of the active infection and markers of adult worms burden (More & Coopermann 1990, Chanteau et al 1994, McCarthy et al 1995, Weil et al 1996, Rocha et al 1996.…”
mentioning
confidence: 99%
“…Evidently, our results are in parallel with earlier findings where the levels of circulating antigen were monitored for a period of 18 months in endemic areas of other parts of the world and it remained unaltered. This suggests that Og4C3 antibody appears to recognize a particular antigen released by the adult worm (8). Currently such long term follow up of the MF patients using Og4C3 monoclonal antibody based ELISA is in progress in our laboratory.…”
Section: Resultsmentioning
confidence: 93%